UNDERSTANDING IMPULSIVE BUYING IN LIVE-STREAMING COMMERCE: THE ROLE OF STREAMER-DISPLAYED EMOTIONS, CUSTOMER ENGAGEMENT, AND TIME PRESSURE - Hendri Triyanto; Budhi Haryanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of streamers’ positive emotional expressions specifically pleasure and arousal in shaping impulsive purchasing behavior in TikTok live-streaming commerce. Guided by the Stimulus–Organism–Response (S-O-R) framework, the model positions customer engagement as an intervening variable, while perceived time pressure is incorporated as a boundary condition influencing the relationships. Data were collected through a survey of 260 Generation Z consumers (aged 18–29) who had recently engaged in purchasing via TikTok live streams. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both emotional dimensions significantly enhance customer engagement, with arousal showing a more dominant influence. Increased engagement, in turn, leads to a higher tendency toward impulsive buying, highlighting its role in translating emotional stimuli into behavioral outcomes. While pleasure also directly affects impulsive purchasing, its effect is comparatively less pronounced. Interestingly, perceived time pressure weakens the relationship between engagement and impulsive buying, suggesting that excessive urgency may discourage spontaneous purchasing decisions. Overall, this study enriches the literature by reinterpreting streamer-generated emotions as external stimuli and by revealing the nuanced role of time pressure in live-streaming commerce. The findings also provide actionable insights for optimizing live-streaming strategies in social commerce environments.